Cap n collar transcription factor regulates multiple genes coding for proteins involved in insecticide detoxification in the red flour beetle, Tribolium castaneum. (November 2017) - Kalsi, Megha; Palli, Subba Reddy
Abstract: In invertebrates, a heterodimer of xenobiotic transcription factors, cap n collar C isoform (CncC) and muscle aponeurosis fibromatosis (Maf) mediate cellular defense. In insects, these proteins regulate expression of genes involved in insecticide detoxification. In the current study, we performed sequencing of cDNA copied from RNA isolated from Tribolium castaneum pyrethroid resistant strain (QTC279) beetles injected with CncC or green fluorescence protein (GFP, control) dsRNA. Differential expression analysis of sequences identified 662 genes that showed a decrease and 91 genes that showed an increase in expression (p value ≤ 0.01 and log2 fold change of≥ 1.5) in CncC knockdown insects when compared to their expression in control insects. We selected a subset of 27 downregulated genes and verified their differential expression using qRT-PCR. This subset of 27 genes included 21 genes with a predicted function in xenobiotic detoxification. RNAi and insecticide bioassays were employed to study the function of six of these genes coding for CYP4G7, CYP4G14, GST-1 and four ABC transporters, ABCA-UB, ABCA-A1 and ABCA-A1L and ABCA-9B involved in all three phases of insecticide detoxification. These data suggest that CncC regulates genes coding for proteins involved in detoxification of insecticides. Graphical abstract: Highlights: Differential expression analysis of RNA sequences identified 662 genes are down regulated in CncC knockdown insects. qRT-PCR verified differential expression of 25 out 27 genes tested. CncC regulated genes code for proteins involved in all three phases of insecticide detoxification. RNAi and insect bioassays confirmed the function of six CncC regulated genes in insecticide sensitivity.